(untitled) (Research, Society and Development, 2024)
Objective: To systematically review the evidence on the use of melatonin in the treatment of sleep disorders in children and adolescents with autism spectrum disorder (ASD). Method: Systematic review of randomized controlled clinical trials on the use of melatonin and included children and adolescents with ASD and sleep disorders, searching MEDLINE, SCOPUS, Web of science, Cochrane Central Register Controlled Trials, in the period between September and October 2023. The selection of studies were carried out using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results: Changes in Total Sleep Time (TST) and Sleep Latency (SL) measurements were statistically significant. The 95% CI of 1.66 [1.10, 2.23] and 2.55 [1.02, 4.08] showed an increase in TST with the use of the intervention. (p < 0.00001) [18, 19]. Garstang showed a statistical difference with the use of melatonin, with the result of 95% CI of -5.96 [-8.77, -3.16], as well as Cortesi with a 95% CI of -1.23 [-1.75, - 0.70] and Gringras with -1.35 [-1.79, -0.91], with reduced latency to start sleep (p = 0.0002). Conclusions: Larger samples are needed to evaluate the effectiveness of melatonin on other sleep patterns, such as nighttime awakenings and sleep quality.